(3TQM GdTGajIs - (3aNQ GdOjf CMeO Hf GdMSf GdLGHQOj, GdLGHQOj,J (B746 (3g` s ((3LYaQ Hf CMeO Hf NVQ s)
(3ChdgG (B:s
(3fMeOc jG ef HjOg GdNjQ hGdLhO hdjS ai GdMbjbI ZjQg HehLhO hfUdi Ydi QShdc eMeO s
(3BNQgG (B:s
(3hMJi MedG YdjgG dCfgG HeYfGgG ai GdZGjI hGdGfJgGA hGddg CYde s
(3Vef eLehY , JQJjHgG (B: 3s
(3GdTGajI ai GdUQa dGHf GdMGLHs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B107s
Keywords: (3GdUQas